PERKEMBANGAN FILSAFAT ILMU DAN RELEVANSINYA TERHADAP FILSAFAT ISLAM SEBAGAI MATERI AJAR DI PERGURUAN TINGGI - Ariyanti Rahayu; Hasnah Faizah; Auzar Auzar (Jurnal Ilmu Budaya, 2023)
Explaining the development and relationship between science philosophy and Islamic philosophy is the aim of this writing. Descriptive qualitative is the method used by collecting data through library research to gain the aim. The result shows that the development of science philosophy can not be separated from the history of developed science which is the main base in the development of science in which science philosophy consists of (ontology, epistemology, and axiology) Islamic philosophy is based on Islamic notions led by revelation from Allah which are the absolute truth. Science philosophy is only the trigger since all theories and concepts have already been given in Al-Qur’an. Thus, science philosophy and Islamic philosophy can work together to create science based on absolute truth.